Impact of Integrated Nutrient Management Practices on Soil Biological Properties - Singh Bamboriya, Jitendra; Purohit, H.S.; Jat, Gajanand; Bamboriya, S.D. (The Journal of plant science research, 2022)
Soil microbial community keeps the soil healthy and fertile therefore their optimal presence is needed for sustaining the crop production to meet the basic needs of future generation. Therefore, a nutrient management trial was conducted to find out the best nutrient sources and their combinations which may improve overall soil biological health. Soil samples were collected from 0-15 cm soil depth after harvesting of maize crop during two cropping seasons. The samples were tested in laboratory following standard protocols. Application of PEC combined with 75% of NPK and bio-fertilizers inoculation is a good strategy to improve soil biological quality for sustainable agriculture.